2023
DOI: 10.1111/gcb.16914
|View full text |Cite
|
Sign up to set email alerts
|

TreeGOER: A database with globally observed environmental ranges for 48,129 tree species

Roeland Kindt

Abstract: The TreeGOER (Tree Globally Observed Environmental Ranges) database provides information for most known tree species of their environmental ranges for 38 bioclimatic, eight soil and three topographic variables. It is based on species distribution modelling analyses of more than 44 million occurrences. The database can be accessed from https://doi.org/10.5281/zenodo.7922927. Statistics that include 5% and 95% quantiles were estimated for a cleaned and taxonomically standardized occurrence data set with differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…In ecological context, Hughes et al (1996a) analysed the natural distributions of 819 eucalypt taxa and found that 41% and 25% of the eucalypt species have a mean annual temperature range of less than 2°C and 1°C, respectively. Hence, a range of approaches have been used to improve our knowledge of the climatic niche occupied by eucalypt species worldwide (Kindt, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In ecological context, Hughes et al (1996a) analysed the natural distributions of 819 eucalypt taxa and found that 41% and 25% of the eucalypt species have a mean annual temperature range of less than 2°C and 1°C, respectively. Hence, a range of approaches have been used to improve our knowledge of the climatic niche occupied by eucalypt species worldwide (Kindt, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…SDMs use species occurrence records and environmental conditions to estimate the potential geographic ranges and suitable habitats for species ( Booth et al, 2014 ; Box, 1981 ; Elith et al, 2011 ; Hutchinson, 1957 ; Phillips et al, 2006 ). These models play a crucial role in conservation and restoration planning by helping predict how changes in land use and climate impact species distributions ( Kindt, 2023 ; Porfirio et al, 2014 ; Urban et al, 2016 ). While species presence/absence data—which needs extensive surveys by experts—is limited, presence-only data—which can be obtained from communities’ observations—is much more available.…”
Section: Introductionmentioning
confidence: 99%